Short-Term Groundwater Level Fluctuations Drive Subsurface Redox Variability - Machado-Silva, Fausto; Weintraub, Michael N; Ward, Nicholas D; Doro, Kennedy O; Regier, Peter J; Ehosioke, Solomon; Thomas, Shan Pushpajom; Peixoto, Roberta B; Sandoval, Leticia; Forbrich, Inke; Kemner, Kenneth M; O'Loughlin, Edward J; et al. (Environmental science & technology, 2024)
As global change processes modify the extent and functions of terrestrial-aquatic interfaces, the variability of critical and dynamic transitional zones between wetlands and uplands increases. However, it is still unclear how fluctuating water levels at these dynamic boundaries alter groundwater biogeochemical cycling. Here, we used high-temporal resolution data along gradients from wetlands to uplands and during fluctuating water levels at freshwater coastal areas to capture spatiotemporal patterns of groundwater redox potential ( ). We observed that topography influences groundwater that is higher in uplands than in wetlands; however, the high variability within TAI zones challenged the establishment of distinct redox zonation. Declining water levels generally decreased , but most locations exhibited significant variability, which is associated with rare instances of short-term water level fluctuations, introducing oxygen. The -oxygen relationship showed distinct hysteresis patterns, reflecting redox poising capacity at higher , maintaining more oxidizing states longer than the dissolved oxygen presence. Surprisingly, we observed more frequent oxidizing states in transitional areas and wetlands than in uplands. We infer that occasional oxygen entering specific wetland-upland boundaries acts as critical biogeochemical control points. High-resolution data can capture such rare yet significant biogeochemical instances, supporting redox-informed models and advancing the predictability of climate change feedback.